East Antarctic Ice Sheet–Southern Ocean Interactions in Prydz Bay region from the Middle Miocene to the Present - Evangelinos,D; van,de Flierdt T; Pena,LD; Paredes,E; Cacho,I; Escutia,C (2025)
Understanding Southern Ocean-Antarctic Ice Sheet (AIS) interactions in the geological past is crucial for evaluating the sensitivity of the ice sheet to ocean forcing during future climate warming and predicting its contribution to future sea-level rise. Geological evidence indicates the onset of a modern-like strong Antarctic Circumpolar Current (ACC) in the Late Miocene (~10 million years ago). However, the response of the East Antarctic Ice Sheet to these changes remains poorly constrained. In this study, we present neodymium and strontium isotope compositions of fine-grained (